RI 4210 Black Rock Tungsten Deposit, Mono Co., Calif. - Leon W. Dupuy (The National Institute for Occupational Safety and Health (NIOSH), 1948)
"INTRODUCTION Scheelite occurring in tactite at the Black Rock tungsten mine, near Benton in Mono County, Calif., was investigated by the Bureau of Mines in cooperation with the Geological Survey as part of their search for additional sources of supply of strategic minerals authorized under the Strategic Materials Act. 3/4/The work accomplished by the Bureau, and the assays of samples taken are described in this manuscript. The ore found aided materially in prolonging the operating life of the mine during the recent national emergency, supplying much-needed tungsten for war use. ACKNOWLEDGMENTSIn its program of investigations of mineral deposits, the Bureau of Mines has as its primary objective the more efficient utilization of our mineral resources to the end that they make the greatest possible contribution to national security and economy. The Mining Division, under the direction of Lowell B. Moon, chief, conducts preliminary examinations, performs the actual development work, and prepares the final report. The Metallurgical Division, under the direction of C. C. Ralston, chief, analyzes samples and performs beneficiatibn tests."